32 Bacterial Communities in the Uterus and Rumen of Beef Heifers Throughout Development with Protein Supplementation. (8th March 2022) - Ault-Seay, Taylor B; Brandt, Kiernan; Henniger, Madison T; Mathew, Daniel; Moorey, Sarah; Schrick, F Neal; Pohler, Ky G; Rhinehart, Justin D; Schneider, Liesel G; McLean, Kyle J; Myer, Phillip R
Abstract: Protein supplementation to replacement heifers is utilized to reach targeted body weights, which may affect the animal's gut and reproductive microbiomes and potentially impact breeding outcomes. The objective of the study was to evaluate the effects of protein supplementation on the ruminal and uterine bacterial communities of developing heifers. Thirty-nine pre-pubertal commercial Angus heifers were blocked by body weight (BW) and randomly assigned to one of three supplementation groups: 10% crude protein (CP), 20% CP, or 40% CP. Supplements were provided four times weekly for 140d. Blood and BW were taken every 14d to monitor development. Every 56d, uterine flushes and rumen content were collected for bacterial identification. Uterine flushes were collected via 20 mL sterile saline flushed through a Foley catheter, and rumen content by esophageal tubing. Bacterial DNA was extracted and amplified targeting the V1-V3 region of the 16S rRNA gene. Microbiome analyses were performed in R 4.1 with dada2 and phyloseq packages. Statistical analyses were performed in R and SAS 9.4. The GLIMMIX procedure was used including fixed effects of protein, month, and pubertal status. Random effects included BW, interaction of BW and protein, and heifer within the interaction, with repeated measures of month. Alpha diversity differed by month in the rumen, and by month and pubertal status in the uterus (P < 0.05). Bray Curtis analyses indicated clustering by month and pubertal status (P < 0.001) in the uterus, and by month in the rumen (P < 0.001). Multiple uterine and ruminal bacteria abundances differed over time and by protein supplementation and pubertal status (P < 0.05). The impact of pubertal status and month of development may indicate maturation of the uterine bacterial communities through development. Protein supplementation affecting the uterine bacterial communities may provide opportunity to manipulate the uterine microbiome, potentially affecting future reproductive success.